Exploring lived experiences of familial support in forensic settings using best-fit framework synthesis and interpretative phenomenological analysis: a portfolio thesis - Gillespie, Martha Eleanor (The University of Edinburgh, 2019)
Existing research has evidenced the fact that maintained familial support can have positive outcomes for prisoners and forensic patients during a detention. Maintained familial support has been linked with reduced reoffending, improved mental health, and improved relationships following imprisonment or hospitalisation for the individuals receiving support. Despite this, visiting relatives in prison has been shown to have both positive and negative consequences for families of prisoners. Given the available literature which has focused on families’ experiences of supporting relatives during imprisonment, a systematic review was conducted to explore, collate, and critically analyse these findings. Drawing upon qualitative literature, a best-fit framework synthesis approach was used which allowed the researchers to identify the applicability of and expand upon an existing framework when considering families’ experiences. Three superordinate themes were identified: Experiencing a “parallel sentence” beyond prison walls; Shifting roles and relationships; and Ambivalence. Twelve subthemes were encapsulated by these superordinate themes. Whilst literature has explored families’ experiences in this context, there has been a dearth of research exploring prisoners’ perspectives of maintained familial support, and research exploring patients’ experiences of familial support is almost entirely absent. Therefore, an explorative study drew upon the methodological principles of interpretative phenomenological analysis to investigate this phenomenon. Eleven patients residing in a high security forensic hospital who had maintained familial support via hospital visits were interviewed about their experience of familial support. Interviews were recorded, transcribed, and then analysed. Analysis revealed four superordinate themes: Connection; Growth, Power; and Ambivalence. Sixteen subthemes are subsumed by these superordinate themes. Results are discussed, along with clinical implications, study limitations, and suggestions for further research.
Keywords: prisoners; family visits; outcome; reoffence rates; families’ experiences; familial support; high security forensic hospital experience